Electromagnetic Gyrokinetic Simulation of Tokamak Plasma with Semi-Lagrangian Scheme (Communications in Computational Physics, 2025)
The re-splitting $δf$ method (Ye et. al CPC 2020) has been implemented intothe global semi-Lagrangian gyrokinetic code NLT (Lei Ye et al. 2016, JCP) for thesimulations of electromagnetic micro-turbulence in tokamak plasmas. The re-splittingmethod can be incorporated with the numerical Lie transform method, which is anessential numerical scheme for NLT code, to mitigate the cancellation problem appearsin the gyrokinetic $p_{||}$-formulation with gyrokinetic ions and drift-kinetic electrons.With this method, the ion temperature gradient mode (ITG), the kinetic ballooningmode (KBM) and trapped electron mode (TEM) are simulated by NLT and the resultsare well benchmarked with other gyrokinetic simulation codes.